HUBUNGAN PENGETAHUAN PADA IBU HAMIL TRIMESTER III DENGAN PENGGUNAAN KB IUD (INTRA UTERINE DEVICE) PASCA PLASENTA DI KOTA YOGYAKARTA - ASNITA SINAGA (LP2MTBM MAKARIOZ, 2019)
In accordance with RI Law No. 36/2009 on Health, article 78 states that health services in family planning are intended to regulate pregnancy for fertile age couples to form healthy and smart future generations and that the government is responsible and guarantees the availability of personnel, service facilities, counseling , tools and medicines in providing quality family planning services that are safe and affordable by the community. Various businesses in the field of the KB movement as one of the main activities for the development of a prosperous family have been carried out by the government, private sector, and the community itself. One of them is by socializing the latest post placenta IUD contraception method by BKKBN. The Post-Placenta IUD method has its own advantages, besides its installation is more effective because it is done after the placenta is born while reducing the morbidity of the mother. In the results of the expert meeting in 2009 it was said that the use of post placenta and post abortion IUDs should continue to be promoted because it is very effective, bearing in mind the average birth rate of 4,000,000 per year (BKKBN, 2010). In general, the factors that influence mothers are age, education, occupation, parity, in the stability of mothers choosing family planning). The community considers women who have age> 35 years feel old so that the possibility of a pregnancy occurring is very small impact on the occurrence of unmet need. For someone who is more educated will have more extensive knowledge compared to a low level of education. Work can affect the incidence of family planning use, due to busyness and lack of opportunities in accessing contraception. Parity / number of children influences someone in using contraception (BKKBN, 2015, Handayani, 2010).